International criminal justice as a transnational field: rules, authority and victims - Dixon, Peter (International journal of transitional justice, 2013)
This article develops a framework for understanding what international criminal justice (ICJ) is, how it works and why it is arguably the most influential approach to transitional justice. More than just a mechanism in transitional justice’s toolkit, ICJ is a ‘field’ in itself that has developed at the intersection of three other well-established global fields: interstate diplomacy, criminal justice and human rights advocacy. ICJ draws on the rules and practices of these fields, operating as a central site for the use and exchange of the delegated, legal, moral and expert authority active in them. It can thus mobilize authority in ways that make it more powerful at a global level than ‘place-based’ approaches to transitional justice. We illustrate this through a discussion of the victim of international crimes - a figure integral to the rules of ICJ and an increasing focus of the field, despite the fact that victims wield very little authority within the field.